Działalność mikroprzedsiębiorstw w gospodarce polskiej - Wolak-Tuzimek, Anna (Micro Enterprise Activity in Polish Economy, 2007)
The paper presents the statistical analysis of micro enterprises in Polish economy in the years 1999--2004. The paper presents changes of micro enterprises amount as well as changes of their legal form and the profile of activity. It also provides the number of the micro enterprises employees respectively to the county. The study proves that the salary in the micro enterprise depends on many different factors, i.e. the profile of the enterprise, its legal form or geographical situation. While analyzing the enterprise economic results, the tendencies and dependence on the chosen factors have been described. The author notices that the micro enterprises had their best results in the year 2004. Although the number of the micro enterprises decreased in about 0.6% their incomes increased in 26%.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 639-647